TRESEARCH ON THE INHERITANCE, DEVELOPMENT AND COMPETITIVE REFORM OF MARTIAL ARTS SHORT SOLDIERS FROM THE PERSPECTIVE OF TRADITIONAL NATIONAL SPORTS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Martial Arts Short Soldiers (short-weapon combat) is an important component of traditional Chinese martial arts and a representative form of traditional national sports. In recent years, with the promotion of standardized competition rules and modern sports systems, Martial Arts Short Soldiers has gradually transformed from a traditional combat practice into a modern competitive sport. However, this transformation has also brought challenges related to cultural inheritance, technical authenticity, and competitive orientation. From the perspective of traditional national sports, this paper systematically analyzes the historical inheritance, contemporary development, and competitive reform of Martial Arts Short Soldiers. By examining its cultural value, developmental dilemmas, and reform pathways, this study proposes strategies for achieving a balanced integration of tradition and modern competition, thereby promoting the sustainable development of Martial Arts Short Soldiers in both cultural and athletic dimensions.